2016
DOI: 10.1142/s0219467816500194
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical Features and Active Appearance Model Applied to Facial Expression Recognition

Abstract: One of the most effective ways of expressing emotion is through facial expressions. This work proposes and discusses a geometrical descriptor based on the calculation of distances from coordinates of facial fiducial points, which are used as features for training support vector machines (SVM) to classify emotions. Three data sets are studied and six basic emotions are considered in our experiments. In comparison to other approaches available in the literature, the results obtained with our geometrical descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The geometric method uses the absolute and relative geometrical relationship of facial components for feature extraction. Two well-known model-based facial feature point detection methods are an Active Shape Model (ASM) (Cootes, Taylor, Cooper, & Graham,1995;Shbib, & Zhou, 2015) and an Active Appearance Model (AAM) (Edwards, Cootes, & Taylor, 1998;Maximiano da Silva, &Pedrini, 2016). The main drawback of the statistical model is the model fitting.…”
Section: Related Workmentioning
confidence: 99%
“…The geometric method uses the absolute and relative geometrical relationship of facial components for feature extraction. Two well-known model-based facial feature point detection methods are an Active Shape Model (ASM) (Cootes, Taylor, Cooper, & Graham,1995;Shbib, & Zhou, 2015) and an Active Appearance Model (AAM) (Edwards, Cootes, & Taylor, 1998;Maximiano da Silva, &Pedrini, 2016). The main drawback of the statistical model is the model fitting.…”
Section: Related Workmentioning
confidence: 99%
“…Static-or frame-based methods categorize the emotion from still images embodying the momentary appearance of the FE, generally in its peak form. Silva et al [17] presented a compact and effective description of face depicting an FE based on horizontal and vertical distance between distinct fiducial points whose locations were known a priori. In one of the experiments, they integrated this geometric feature vector with Gabor filters to extract appearance features and demonstrated that complementing the two features enabled a better discrimination between different emotions.…”
Section: Related Workmentioning
confidence: 99%
“…First, geometric features based on the edges of specific fiducial points from different facial parts and second, appearance based features to represent the muscular texture of the face using change of wrinkles and creases. Study of the FER methods, applied on geometric based features are Active Appearance Model (AAM) [6], elastic bunch graph matching (EBGM) [7], and straight-line distances [8] of fiducial points. On the other hand, appearance based feature extraction techniques are Local Fisher Discriminant Analysis (LFDA) [9], local binary patterns (LBP) [10] and recently Convolutional Neural Networks (CNN) [11].…”
Section: Introductionmentioning
confidence: 99%